Microwave-assisted synthesis of carbon dots–zinc oxide/multi-walled carbon nanotubes and their application in electrochemical sensors for the simultaneous determination of hydroquinone and catechol. Issue 116 (15th December 2016) - Yan, Yaru; Huang, Qitong; Wei, Chan; Hu, Shirong; Zhang, Hanqiang; Zhang, Wuxiang; Yang, Weize; Dong, Peihui; Zhu, Menglin; Wang, Zhaoming
Abstract : Cyclic voltammetry of HQ and CC recorded on Nafion/CDs–ZnO/MWCNTs/GCE. Abstract : A facile, efficient, and rapid microwave-assisted synthesis was developed to prepare carbon dots–zinc oxide/multi-walled carbon nanotubes (CDs–ZnO/MWCNTs) composite. The CDs–ZnO/MWCNT material was characterized by scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD). The electrode modified with the CDs–ZnO/MWCNTs composite was applied for the simultaneous determination of hydroquinone (HQ) and catechol (CC) in 0.1 M phosphate buffer solution (PBS, pH = 4.5). The anodic potential difference (Δ E pa ) between HQ and CC was 104 mV, which indicated that the modified electrode could simultaneously detect HQ and CC. The calibration curves for both HQ and CC were obtained in the range from 5.0 to 200 μM, and the detection limits (S/N = 3) were 0.02 μM and 0.04 μM, respectively. The modified electrode was applied to determine HQ and CC in tap water and the recovery rates were 99.3–105.4% for HQ and 104.3–110.1% for CC.